The monitoring, refurbishment and remediation of existing bridge bearings - Antoniou, Klitsa; Percy, R.A. (My University, 2022)
This paper examines a case study in which bridge bearings were monitored, remediated, and refurbished to extend their working life. The structure concerned lies on the M25 London orbital motorway, constructed during the 1980s in the UK. A series of age-related bearing defects were discovered during the regular inspection and monitoring process. Low-cost monitoring, including time-lapse video cameras and target surveys enabled the short and long term strategy for bearing interventions to be determined, and minimised the need for a major intervention. A series of trials to refurbish the bearings were undertaken to select the most effective methodologies to be deployed on the structure’s bearings. This case study illustrates how cost-effective bridge bearing monitoring may be deployed to determine the maintenance and intervention strategy and how refurbishment may prolong the bearings’ life by improving their performance in allowing for longitudinal movement.